Evaluation of a Program of Pharmaceutical Care to Patients with Type 2 Diabetes Mellitus - Maidana, G. M.; Lugo, G. B.; Vera, Z.; Perez, S.; Mastroianni, P. C. [UNESP] (Fundacion Pharmaceutical Care Espana, 2016)
Introduction: Pharmaceutical Care is the responsible provision of pharmacotherapy for the purpose of achieving concrete results in order to improve the quality of life of patients. Objective: To evaluate the impact of pharmaceutical intervention in patients with Type 2 Diabetes Mellitus. With this aim, the following aspects were analyzed at the beginning and at the end of the study: glycemia, glycosylated hemoglobin, quality of life of the patients, their diabetes knowledge, current medications and initial medicine-related problems and the ones that were solved during the study. Methodology: It was carried out a random clinical trial in which some variables were measured before and after it. It was a non probabilistic and conveniently trial. 32 patients of the intervention group and 32 at a control group participated on it. Monthly interviews were performed in a period of 6 months of pharmaceutical intervention (from October 2011 to June 2012). In this period, only 3 dropouts were recorded. Results: The age of the patients was 55.6 +/- 10.6 years. The patients of the intervention group improved glycemia in 34%; 24 patients showed a value of (<= 130 mg/dL); glycosylated hemoglobin improved in 1.9%; 15 patients reached the desired parameters (<= 6.5%). The life quality of the intervention group increased from 56.3 to 71.3%. On the contrary, in the control group it decreased from 57.4 to 46.1 %. Within the intervention group were found 80 drug-related problems in 27 patients. 59 were solved. At the end of the research, 12 patients solved all their drug-related problems. 254 pharmaceutical interventions were performed. The level of patients' knowledge related to their disease improved by 41% and the knowledge about their medication improved by 53%. Conclusion: It was demonstrated that pharmaceutical interventions helped improving the life quality, the clinical parameters of glycemia, glycosylated hemoglobin and the use of medicines. On the other hand, they lowered drug-related problems and increased patients' satisfaction.
Keywords: Pharmaceutical Care; Type 2 Diabetes Mellitus; Pharmaceutical Intervention